The dispensable nation American foreign policy in retreat - Naṣr, Walī Riḍā 1960- (Anchor Books, 2014)
"Former State Department advisor for Afghanistan and Pakistan and bestselling author Vali Nasr delivers a sharp indictment of America's flawed foreign policy and outlines a new relationship with the Muslim world and with new players in the changing Middle East. In this essential new book, Vali Nasr argues that the Obama administration had a chance to improve its relations with the Middle East, but instead chose to pursue its predecessor's questionable strategies there. Nasr takes readers behind the scenes at the State Department and reveals how the new government's fear of political backlash and the specter of terrorism crippled the efforts of diplomatic giants, like Richard Holbrooke and Hillary Clinton, to boost America's foundering credibility with world leaders. Meanwhile, the true economic threats, China and Russia, were quietly expanding their influence in the region. And a second Arab Spring is brewing...not a hopeful clamor for democracy but rage at the United States for its foreign policy of drones and assassinations. Drawing on his in-depth knowledge of the Middle East and firsthand experience in diplomacy, Nasr offers a powerful reassessment of American foreign policy that directs the country away from its failing relationships in the Middle East (such as with Saudi Arabia) toward more productive, and less costly, partnerships with other foreign allies (such as Turkey). Forcefully persuasive, Vali Nasr's book is a game changer for America as it charts a course in the Muslim world, Asia, and beyond. "..
Includes bibliographical references and index
Keywords: Außenpolitik; Naher Osten; USA; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- Islamic countries; Islamic countries -- Foreign relations -- United States; Arabische Staaten